6x-(3x+8)=5x-(4-6x)

Simple and best practice solution for 6x-(3x+8)=5x-(4-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(3x+8)=5x-(4-6x) equation:


Simplifying
6x + -1(3x + 8) = 5x + -1(4 + -6x)

Reorder the terms:
6x + -1(8 + 3x) = 5x + -1(4 + -6x)
6x + (8 * -1 + 3x * -1) = 5x + -1(4 + -6x)
6x + (-8 + -3x) = 5x + -1(4 + -6x)

Reorder the terms:
-8 + 6x + -3x = 5x + -1(4 + -6x)

Combine like terms: 6x + -3x = 3x
-8 + 3x = 5x + -1(4 + -6x)
-8 + 3x = 5x + (4 * -1 + -6x * -1)
-8 + 3x = 5x + (-4 + 6x)

Reorder the terms:
-8 + 3x = -4 + 5x + 6x

Combine like terms: 5x + 6x = 11x
-8 + 3x = -4 + 11x

Solving
-8 + 3x = -4 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-8 + 3x + -11x = -4 + 11x + -11x

Combine like terms: 3x + -11x = -8x
-8 + -8x = -4 + 11x + -11x

Combine like terms: 11x + -11x = 0
-8 + -8x = -4 + 0
-8 + -8x = -4

Add '8' to each side of the equation.
-8 + 8 + -8x = -4 + 8

Combine like terms: -8 + 8 = 0
0 + -8x = -4 + 8
-8x = -4 + 8

Combine like terms: -4 + 8 = 4
-8x = 4

Divide each side by '-8'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 8k+12-2=6 | | (8x-16)+(4x+20)= | | -4(5y-7)+3(2y+8)= | | u^2+16u+36=0 | | (4a^3+a-8)-(7-8a^3+3a^2)= | | 1/4(5-1)+6=7/8(3*5-7) | | x+x+11+x+11+8=84 | | 7/4(3j+5)+1=15 | | 14s+.99+.99=20.18 | | X^2-e^2=0 | | x-.14(x)=255.10 | | 1/3(2c-5)+3=7 | | n+50*2=440 | | -3x+2=-7x | | 2/7y=6 | | -5=13x^2 | | n+50*2=220 | | -3(2q-5)=3q+6 | | f(x)=x^2-7x-18 | | 4(b-1)-7=17 | | 3x+2=-7x | | 5x+3=2x+33 | | 3r+5/2+2=12-2r | | x-(-5/12)=-5/12 | | n+50/2=220 | | 6x+2=10x-10 | | -64x^8+100x^6=0 | | 9.1t-2.6=6.5 | | n*2+20=180 | | (9x+5)+(x+8)= | | 1.5=a/3 | | 1.7n+97.2=-n |

Equations solver categories